Hormone imbalances detected in study participants with pre-diabetes in a Durban-based clinical setting, South Africa - Sosibo, Aubrey M.; Mzimela, Nomusa C.; Ngubane, Phikelelani S.; Khathi, Andile (International journal of diabetes in developing countries, 2025)
Background Type II diabetes mellitus onset is linked with hormonal imbalances. However, the knowledge about hormonal alterations in pre-diabetes is limited. Objective The study aimed to examine type II diabetes mellitus-associated hormone levels during the pre-diabetes phase in participants aged 25–45 in a Durban-based clinical setting in South Africa. Methods Stored plasma samples from a retrospective study collected 364 samples that were divided into pre-diabetes and non-pre-diabetes groups. From the 364, 38 samples from the group of persons without pre-diabetes and 38 from persons with glycated haemoglobin determined pre-diabetes were blindly selected. The hormone concentrations (C-peptide, cortisol, adipokines, thyroids, incretins, and sex steroids) of the study participants were measured using the BIO-RAD Bio-Plex MAGPIX instrument. Results Hormone imbalances in several hormones were detected in study participants with pre-diabetes. Most of the hormone dysregulation associated with T2DM begins in pre-diabetes but at a moderate level. Conclusion The findings reveal new possible hormone therapy targets for pre-diabetes and contribute to the growing support for targeting pre-diabetes as a preventative measure for T2DM prevention.